AB0767 Comparison of Inraarticular and Intracyst Corticosteroid Injections in the Treatment of Baker's Cyst with Ultrasonographic Follow-Up. (10th June 2014) - Bal, A.; Sancıoglu, H.; Tezel, N.; Erdogdu, D.; Karaahmet, O.; Cakci, A.
Abstract : Background: A Baker's cyst is an enlargement of the gastrocnemius-semimembranosus bursa in the knee that usually communicates with the joint. Ultrasonographical examination is important for differentiation of Baker's cyst from other pathologies such as aneurysms of the popliteal artery, synovial sarcoma, and ganglia of the popliteal tendon. In addition, ultrasonography may provide guidance for safe injections. Treatment options are physical therapy, aspiration and korticosteroid injection, and surgery (1, 2). Objectives: The purpose of this study was to compare the effectiveness of intraarticular and intracyst corticosteroid injections for the treatment of Baker's cyst using ultrasonographic evaluation and guidance. Methods: Fifty-five patients with a clinical suspicion of Baker's cyst were evaluated with B-mode ultrasonography using a 7–13 MHz linear probe. Of these, 38 patients who were diagnosed with a Baker's cyst, is secondary to osteoarthritis were randomized into 2 groups based on injection type. The maximum transverse and longitudinal cyst areas were measured by ultrasonography, and disability was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) at the first examination and again 2 and 6 weeks later. Under ultrasonographic guidance during the first examination, the Baker's cyst was aspirated directly, and 40 mg triamcinolonehexacetonide was administered via intraarticular injection (group 1) or intracyst injection (group 2). Results: There was a significant reduction from baseline in the WOMAC scores and transverse and longitudinal cyst areas in both groups at week 2, while only the WOMAC scores were significantly lower in both groups at week 6 (all p<0.01). Compared to baseline, significant reductions in the transverse and longitudinal cyst areas at week 6 were only observed in the intraarticular injection group (both p<0.01), but not the intracyst injection group (both p>0.05). There was not observed any side effect. Conclusions: Ultrasonography enables the diagnosis, follow-up, safe aspiration, and safe injection of Baker's cysts. Corticosteroid administered via both intraarticular and intracyst injections are effective for reductions in cyst area, pain, and disability associated with Baker's cysts; however, based on these results, intraarticular injections appear to be more effective especially in the long term. References: Di Sante L, Paoloni M, Loppolo F et al. ULltrasound guided aspiration and corticosteroid injection of Baker's cyst in knee osteoarthritis: a prospective observational study. Am J Phys Med Rehabil. 2010; 89: 970-5. Bandinelli F, Fedi R, Generini S et al. Longitudinal ultrasound and clinical follow-up of Baker's cyst injection with steroids in knee osteoarthritis. Clin Rheumatol. 2012; 31: 727-31. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4138